Conventional versus minimal ovarian stimulation: an intra-patient comparison of ovarian response in poor-responder women according to Bologna Criteria. Issue 4 (October 2018) - Labarta, Elena; Marin, Diego; Remohí, José; Bosch, Ernesto
Key message: In poor-responder patients according to Bologna criteria, minimal ovarian stimulation seemed to be a good alternative when conventional stimulation failed or even as a first-line treatment, as the former offered a better ovarian response and number of good-quality embryos while using lower doses of gonadotrophins. Abstract: Research question: Is minimal ovarian stimulation (MOS) as effective as conventional ovarian stimulation (COS) in ovarian response and embryo quality in the same 46 poor-responder patients according to the Bologna criteria? Design: An intra-patient comparison of patients undergoing both protocols. Ovaries were stimulated with either a gonadotrophin-releasing hormone antagonist protocol and a combination of recombinant FSH and highly purified human menotrophin (HP-HMG) daily (COS), or with the use of clomiphene citrate 50 mg daily and 150 IU of HP-HMG or recombinant FSH every other day from simulation day 4 (MOS). Results: After MOS, significantly more good-quality embryos (1.0 ± 1.2 versus 0.3 ± 0.6) ( P = 0.002), oocytes (3.2 ± 1.9 versus 2.0 ± 1.8) ( P = 0.002), and mature (metaphase II) oocytes (2.6 ± 1.7 versus 1.6 ± 1.7) ( P = 0.001) were obtained. In COS cycles, a significantly higher total gonadotrophin dose was needed per good-quality embryo (+2194 IU; 95% CI 618 to 3170). Conclusions: In poor responder patients, MOS is a good alternative when COS has failed, or even as a first-line treatment. It offered a significantly greater number of good-quality embryos as well as a higher number of oocytes, using significantly lower doses of gonadotrophins per oocyte and embryo obtained.